2005
DOI: 10.1007/s00442-005-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of range position, inter-annual variation and density on demographic transition rates of Hornungia petraea populations

Abstract: The central-marginal model assumes unfavourable and more variable environmental conditions at the periphery of a species' distribution range to negatively affect demographic transition rates, finally resulting in reduced population sizes and densities. Previous studies on density-dependence as a crucial factor regulating plant population growth have mainly focussed on fecundity and survival. Our objective is to analyse density-dependence in combination with the effect of inter-annual variation and range positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…Discussion Examination of detailed individual-level annual census data from natural populations has revealed marked differences in population dynamics between central and marginal areas of species' ranges. More studies have examined vital rate mean differences across the range than differences in temporal variability (33,35,36). Using a sequence of 7 annual transitions, this study shows that central and marginal populations differ not just in mean vital rates but in some cases also in the temporal variabilities of vital rates.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Discussion Examination of detailed individual-level annual census data from natural populations has revealed marked differences in population dynamics between central and marginal areas of species' ranges. More studies have examined vital rate mean differences across the range than differences in temporal variability (33,35,36). Using a sequence of 7 annual transitions, this study shows that central and marginal populations differ not just in mean vital rates but in some cases also in the temporal variabilities of vital rates.…”
Section: Resultsmentioning
confidence: 85%
“…Paradoxically, populations at the M. cardinalis range center exhibit long-term growth rates that are below replacement levels, whereas marginal population growth rates encompass values consistent with population stability. Several other comparisons of central-marginal demographic patterns have found similarly ambiguous or unexpected results (35)(36)(37)(38)(39), which suggests that consideration of additional factors such as density dependence, source-sink dynamics, dispersal limitation, and disequilibrium between climate and current ranges will be necessary to fully understand the relationship between demography and distribution (39).…”
Section: Resultsmentioning
confidence: 99%
“…For a therophyte plant, the transition from seed in the seed bank to seedling or juvenile may depend on the initial seed density, while the transition from juvenile to reproductive adult and from adult plant to seed might depend on the corresponding density in the population (Kluth and Bruelheide 2005). Therefore, changes in the ratio of reduced to oxidized inorganic N may have prevented therophyte plants from using the increased N availability to complete their life cycle (van den Berg et al 2008) in the first and/or second years of N addition.…”
Section: Short-term Response Of a N-limited Ecosystem To Increased N mentioning
confidence: 99%
“…Peripheral populations may occur in locally favourable conditions (Lennon et al 2002), such as high water availability, high soil organic matter content or low competition. While some studies have found lower fecundity (Garc í a et al 2000, Jump andWoodward 2003), recruitment (Tremblay et al 2002) or survival (Carey et al 1995) in peripheral populations, others have reported increased values in diff erent vital rates towards range edges (Kluth and Bruelheide 2005a, Angert 2009, Samis and Eckert 2009). While some studies have found lower fecundity (Garc í a et al 2000, Jump andWoodward 2003), recruitment (Tremblay et al 2002) or survival (Carey et al 1995) in peripheral populations, others have reported increased values in diff erent vital rates towards range edges (Kluth and Bruelheide 2005a, Angert 2009, Samis and Eckert 2009).…”
mentioning
confidence: 98%
“…Demographic performance of populations seems to be indeed rather variable across many species ' ranges (Carey et al 1995, Nantel and Gagnon 1999, Garc í a et al 2000, Kluth and Bruelheide 2005a, Purves 2009), probably refl ecting specifi c local environmental conditions. In addition, populations at the range margin may or may not be considered marginal from an ecological point of view (Grant andAntonovics 1978, Herrera andBazaga 2008).…”
mentioning
confidence: 99%